Fostering professional judgement and decision making in social work education: addressing dilemmas of equal treatment. - Witter, Stefanie Julia (Social Work Education, 2025)
Since social workers are often confronted with dilemmas as insoluble conflicts, professional judgment and decision-making skills are necessary. Therefore, social workers must already be confronted with such conflicts during their education, especially with dilemmas challenging the value of equal treatment: While equality for all clients remains one of the highest mandates in social work, specific cases require unequal treatment for social justice. To assess social work students' ability to recognize such conflicts, two dilemma stories were presented in two quantitative studies, involving a total of 156 participants. The task was to approve or disapprove of decisions, with different grades to filter out extreme views. The results reveal that students hold both perspectives on the equality-related conflicts. Furthermore, about half of the students rate a decision as extremely right or extremely wrong, which indicates that they do not recognize the dilemma as such. These findings highlight the need to address such dilemmas in education while promoting students' ability to weigh up ethical considerations. This research invites us to adapt teaching methods by using the dilemma stories together with the related theoretical parts to foster an understanding of conflicts and prepare future social workers to navigate such ethical challenges.